2016
DOI: 10.1128/mbio.00276-16
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Type II Epithelial Cells Contribute to the Anti-Influenza A Virus Response in the Lung by Integrating Pathogen- and Microenvironment-Derived Signals

Abstract: Influenza A virus (IAV) periodically causes substantial morbidity and mortality in the human population. In the lower lung, the primary targets for IAV replication are type II alveolar epithelial cells (AECII), which are increasingly recognized for their immunological potential. So far, little is known about their reaction to IAV and their contribution to respiratory antiviral immunity in vivo. Therefore, we characterized the AECII response during early IAV infection by analyzing transcriptional regulation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 46 publications
0
47
0
Order By: Relevance
“…These genes included cytokines and chemokines (Cxcl9, Ccl5, IL12b, Ccl8) , IFN response genes (Ifitm6, Ifi27l2a, Ifna2, Ifit2, Ifitm5, Ifra11 ), and genes involved in processing MHC class I antigens (Psmb10, Tap2, H2-Q2, H2-K1, Psmd9, Psme2, Psme1). The significant up-regulation of host defense genes in response to PR8 in the LA4 cell line corresponds with the expression profile of murine type II alveolar epithelial cells in response to PR8 infection in mice [37]. Furthermore, strong up-regulation of immune response-related genes upon PR8 infection of mice correlates with disease severity [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These genes included cytokines and chemokines (Cxcl9, Ccl5, IL12b, Ccl8) , IFN response genes (Ifitm6, Ifi27l2a, Ifna2, Ifit2, Ifitm5, Ifra11 ), and genes involved in processing MHC class I antigens (Psmb10, Tap2, H2-Q2, H2-K1, Psmd9, Psme2, Psme1). The significant up-regulation of host defense genes in response to PR8 in the LA4 cell line corresponds with the expression profile of murine type II alveolar epithelial cells in response to PR8 infection in mice [37]. Furthermore, strong up-regulation of immune response-related genes upon PR8 infection of mice correlates with disease severity [11].…”
Section: Resultsmentioning
confidence: 99%
“…Alveolar epithelial cells have a key role in alerting the immune system to infection by respiratory viruses and shaping immune responses [37, 56, 57]. As viruses from several different families all target respiratory epithelial cells, it is important to understand the similarities and differences in how these cells respond to a diverse set of viruses.…”
Section: Discussionmentioning
confidence: 99%
“…These cells can be identified in enzyme-digested lung tissue using flow cytometry. We defined AT-I as CD45 À , T1a + MHC-I + , AT-II as CD45 À , T1a À , EpCAM + MHC-II high , and cilia cells as CD45 À , T1a À , EpCAM + MHC-II int as previously described (Stegemann-Koniszewski et al, 2016;Cardani et al, 2017;Hasegawa et al, 2017) ( Figure 3A). Although two recent transcriptomic studies identified an IFN gene signature in AT-II (Stegemann-Koniszewski et al, 2016;Steuerman et al, 2018), to the best of our knowledge, the IFN-response in this and other pulmonary epithelial cells has yet to be compared.…”
Section: M1red Mice Reveal That Pulmonary Epithelial Cells Exhibit DImentioning
confidence: 99%
“…Chemokines and chemokine receptors are critical in directing T cells to sites of infection. CXCL9 and CXCL10 from epithelial cells are strongly induced by influenza infection [14, 17]. The receptor for these chemokines, CXCR3, is expressed on activated CD8 T cells and is required for efficient infiltration of the infected respiratory tract [18].…”
Section: Resultsmentioning
confidence: 99%